Jalur Garut - Cikajang: Pengembangan Perkeretaapian di Selatan Jawa Barat Masa Kolonial - Iwan Hermawan (PANALUNGTIK, 2022)
Forced cultivation and its following period successfully increasing income from agricultural products, especially plantations, which then encouraged the development of railroad transportation in Java. The construction of the railway line to Garut was carried out simultaneously with the construction of the Bandung--Cilacap line on the Cicalengka--Cibatu--Garut section. This route was extended to Cikajang and was planned to Pameungpeuk. The problem posed in this paper is the position of the Garut--Cikajang line in the development of the railway in southern West Java during the Dutch colonial period. To answer the problem, a descriptive analytical method with a spatial approach was used. Data collection was carried out through a literature review and field observations. The construction of the Garut--Cikajang line is part of the plan to build a railway line connecting the main route with the southern coast of West Java which is intended to facilitate the transportation of people and products from the South Garut area. The archaeological remains in Cikajang station area shows that this line is part of a grand plan to build a railway line connecting the main line with the southern coast of West Java.